Resveratrol ameliorates 2,4-dinitrofluorobenzene-induced atopic dermatitis-like lesions through effects on the epithelium - Sule Caglayan Sozmen; Meral Karaman; Serap Cilaker Micili; Sakine Isik; Zeynep Arikan Ayyildiz; Alper Bagriyanik; Nevin Uzuner; Ozkan Karaman (PeerJ, 2016)
Background. Resveratrol is a natural polyphenol that exhibits anti-inflammatory effects. The aim of this study was to investigate the effects of resveratrol treatment on epithelium-derived cytokines and epithelial apoptosis in a murine model of atopic dermatitis-like lesions. Material and Methods. Atopic dermatitis-like lesions were induced in BALB/c mice by repeated application of 2,4-dinitrofluorobenzene to shaved dorsal skin. Twenty-one BALB/c mice were divided into three groups: group I (control), group II (vehicle control), and group III (resveratrol). Systemic resveratrol (30 mg/kg/day) was administered repeatedly during the 6th week of the experiment. After the mice had been sacrificed, skin tissues were examined histologically for epithelial thickness. Epithelial apoptosis (caspase-3) and epithelium-derived cytokines [interleukin (IL)-25, IL-33, and thymic stromal lymphopoietin (TSLP)] were evaluated immunohistochemically. Results. Epithelial thickness and the numbers of IL-25, IL-33, TSLP and caspase-3-positive cells were significantly higher in group II compared to group I mice. There was significant improvement in epithelial thickness in group III compared with group II mice (p < 0.05). The numbers of IL-25, IL-33, and TSLP-positive cells in the epithelium were lower in group III than in group II mice (p < 0.05). The number of caspase-3-positive cells, as an indicator of apoptosis, in the epithelium was significantly lower in group III than in group II mice (p < 0.05). Conclusion. Treatment with resveratrol was effective at ameliorating histological changes and inflammation by acting on epithelium-derived cytokines and epithelial apoptosis.